Oral Chronic Mucositis in a Known Lichen Planus Pigmentosus Patient - Dalad Pinchaleaw; Pirawish Limlawan (Case Reports in Dentistry)
Oral manifestations of mucocutaneous inflammatory diseases such as lichenoid dermatoses often affect the patient’s quality of life through the symptoms of pain and burning sensation. In this case report, a patient with known lichen planus pigmentosus (LPP), a variant of lichenoid dermatoses that rarely affect oral mucosa, presented with chronic pain in the oral cavity for 2 months. Her intraoral examination revealed multiple pseudomembranous ulcers with erythematous areas and white striae similar to erosive lichen planus. The histological assessment revealed chronic mucositis, while the direct immunofluorescent examination showed negative results, contradicting the diagnosis of both lichen planus and LPP. Thus, the diagnosis was given as chronic mucositis, and the topical steroid was given. After 6 weeks of steroid application, the lesion resolved. To the best of our knowledge, this is the first report of chronic mucositis in LPP patients. This report could raise the awareness of clinicians to carefully take history as the patient with LPP may suffer from chronic mucositis in the oral cavity as well.